FAKTOR-FAKTOR YANG MENENTUKAN EARNING PER SHARE PADA PT. ADHI KARYA (PERSERO), Tbk - Rudi Bratamanggala; Novita Wizayani (Fakultas Ekonomi Universitas Borobudur, 2020)
This study aims to examine the effect of Return On Equity, Debt to Assets Ratio, Net ProfitMargin, Current Ratio to Earning Per Share at PT. Adhi Karya (Persero) Tbk using multiplelinear regression analysis method. One of the requirements to test multiple linear regressionanalysis is to test the classical assumption. In addition, to assess the goodness of fit of a model,the coefficient of determination, F test, and t test are carried out. This study uses quarterly datafrom 2011 to 2018 for each research variable.The results showed that the variable Return On Equity, Debt to Assets Ratio, Net ProfitMargin, Current Ratio simultaneously had a positive and significant effect on Earning Per Sharewith a Prob (F-statistic) value of 0.000000. Partially, Return on Equity has a positive andsignificant effect with a t-statistic value of 2.092849 and a probability value of 0.0459, thepartial Debt to Assets Ratio has a negative and significant effect with a t-statistic value of -2.615775 and a probability value of 0.0144. Partially, Net Profit Margin has a positive andsignificant effect with a t-statistic value of 3.158318 and a probability value of 0.0039. Partially,Net Profit Margin has a positive and significant effect with a t-statistic value of 2.181700 and aprobability value of 0.0380. In addition, it is found that the adjusted R-squared value is0.718698, this means that 71.86% of the Eaerning Per Share factor can be determined from thefour independent variables. While the remaining 28.14% is influenced by other variables outsidethe research.Keywords: Return On Equity, Debt to Assets Ratio, Net Profit Margin, Current Ratio, EarningPer Share